Game for Awareness of Entrepreneurs in the Protection of their Creations by Intellectual Property: An Experiment in Startup - Silva, Reinaldo Eustaquio; Nunes, Maria Augusta Silveira Netto; Machado, Rita Pinheiro (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Understanding the Intellectual Property (IP) protection landscape helps organizations position themselves in relation to their creations and provides insight into the future direction of a technology, thus directly impacting the three dimensions of Information Systems (IS): Technological, Human and Organizational. From the perspective of the Human Dimension, the lack of knowledge of Information Technology (IT) professionals about this topic can contribute to organizations not protecting their creations by IP. The objective is to verify if the use of the game about IP is effective to aware Startup entrepreneurs in the IT area about the importance of protecting their creations, as well as understanding the most adequate forms of protection in the scope of IP. The Absorptive Capacity. The IP game was performed with 24 employees of an IT Startup, in the second half of 2022. The analysis of the results was carried out with a quantitative approach using descriptive statistics and the paired t-parametric and non-parametric Wilcoxon test Before and after the realization of the game, the students answered a questionnaire with 16 questions, with the purpose of evaluating the learning about the covered contents. The results showed that the game contributed to raising awareness about IP, considering that there was an increase in knowledge. The main contribution of the article is to enable the use of the game in order to stimulate learning about IP by IT professionals. With this, the problem identified regarding the lack of knowledge can be mitigated, thus favoring the dissemination of the IP protection culture.